2000
DOI: 10.1007/pl00006747
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of action of the dual topoisomerase-I and -II inhibitor TAS-103 and activity against (multi)drug resistant cells

Abstract: TAS-103 cytotoxicity is not affected by the presence of Pgp, MRP, LRP or mutations in the CAM binding region of the topo-I enzyme and its growth-inhibitory effect appears to be weakly dependent on exposure duration. The presented evidence suggest that the inhibitory effects of TAS-103 on topo-I and -II may in part be related to its DNA binding rather than primarily through stabilization of topo-I or -II intermediates with DNA through specific binding to the enzymes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…Topo I, as opposed to topo II, is an enzyme that does not depend on the cellular cycle. Moreover, topo I induces cutting of only one DNA helix thread, and topo II induces cutting of one or both of them (Husain et al 1994;Son et al 1998;Minderman et al 2000). There are two isoforms of topo II, the first, topo IIa, weighs 170 kDa, and the second, topo IIß weighs 180 kDa (Krishna & Mayer 2000).…”
Section: Multidrug Resistance Associated Protein -Mrp (Mrp1)mentioning
confidence: 99%
“…Topo I, as opposed to topo II, is an enzyme that does not depend on the cellular cycle. Moreover, topo I induces cutting of only one DNA helix thread, and topo II induces cutting of one or both of them (Husain et al 1994;Son et al 1998;Minderman et al 2000). There are two isoforms of topo II, the first, topo IIa, weighs 170 kDa, and the second, topo IIß weighs 180 kDa (Krishna & Mayer 2000).…”
Section: Multidrug Resistance Associated Protein -Mrp (Mrp1)mentioning
confidence: 99%
“…[4][5][6] Furthermore, TAS-103 effectively inhibited growth of tumor cells in vivo that acquire the resistance against topoisomerase II-targeting agents. [12][13][14][15] Thus, TAS-103 is expected to be used clinically. 16) Cancer chemotherapy is generally accompanied by side effects such as myelosuppression, since the cytotoxic anti-cancer agents damage normal growing cells as well as tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory effects of TAS-103 on topo II catalytic activity was evaluated by Minderman and co-workers. 17 They showed that TAS-103 at concentrations of 24.6 μM and higher inhibits DNA relaxation (as etoposide does) but does not cause the formation of linear DNA species as would be expected for topo II poisons. Compounds 4a,b showed the ability to inhibit enzyme activity at concentrations of 20 μM and higher without formation of linear DNA, suggesting that these compounds might be as potent as TAS-103 for catalytic topo II inhibitors.…”
Section: ■ Introductionmentioning
confidence: 94%
“…Ub possesses two potential binding sites (Met1 and His68), whereas cyt offers three (His26, His33, and Met65). Due to the fact that these samples were diluted with formic acid (0.02% (v/v)) in order to denature the present proteins, they occur in various positively charged states (Ub,(7)(8)(9)(10)(11)(12)(13)(14)cyt,(11)(12)(13)(14)(15)(16)(17)(18)(19). Therefore, deconvolution of the measured spectra was necessary.…”
Section: ■ Introductionmentioning
confidence: 99%